PD-1-inhibitor pembrolizumab for treatment of progressive multifocal leukoencephalopathy - Möhn, Nora (Ther Adv Neurol Disord, 2021)
The reactivation of human JC polyoma virus (JCPyV) results in lytic infection of oligodendrocytes and neuronal cells. The corresponding clinical picture is called progressive multifocal leukoencephalopathy (PML) and results mostly from a disease-related or drug-induced immunosuppression. The opportunistic brain infection leads to a progressive demyelination of multiple areas of the central nervous system. Patients can present with various neurological deficits ranging from slight motoric symptoms to marked aphasia or reduced vigilance. Currently, there is no effective causal therapy for PML. Survival depends on the ability to achieve timely immune reconstitution. If the immune system cannot be restored, PML progresses rapidly and often ends fatally within months. Recently, some evidence for positive response has been reported in patients treated with immune checkpoint inhibitor therapy. Here, we provide a case series of three PML patients with underlying hematological malignancies who were treated with anti-PD-1-antibody pembrolizumab at Hannover Medical School. All patients received an extensive diagnostic follow-up including cerebrospinal fluid analysis, brain imaging, and lymphocyte-phenotyping via flow cytometry. Our patients had very different outcomes, with the only patient showing a specific anti-JCPyV immune response in the sense of an increased JCPyV antibody index clearly benefiting most from the treatment. Our results partly support the hypothesis that anti-PD-1 therapy may represent a promising treatment option for patients with PML. However, there is a current lack of pre-therapeutic stratification regarding the therapeutic response rates. Before larger studies can be initiated to further evaluate the efficacy of anti-PD-1 antibodies in PML, it is imperative to develop a reliable strategy for selecting suitable patients.